Prognosis of Patients With Colorectal Cancer and Apical Lymph Node Metastasis at the Inferior Mesenteric Artery: A Systematic Review and Meta-Analysis - Zhou, Senjun; Shen, Yi; Huang, Chen; Li, Gang (Frontiers in Medicine, 2022)
Background: This review was designed to compile the evidence on the prognosis of patients with colorectal cancer and apical lymph node (APN) metastasis and the long-term benefit of inferior mesenteric artery lymph node (IMA-LN) resection. Methods: We searched the PubMed Central, Cochrane library, EMBASE, and MEDLINE databases from inception until May 2021 for relevant publications. We assess the quality of the studies using the Newcastle Ottawa scale. We conducted a random-effects model meta-analysis and report pooled hazard ratios (HRs) with 95% confidence intervals (CIs). Results: We analyzed data from 13 studies conducted in Japan, China, and Korea with 6,193 participants. Most studies were retrospective in nature and of low quality. We found that patients with APN metastasis had shorter OSs (pooled HR, 2.41; 95% CI, 1.92-3.02) and PFSs (pooled HR, 2.42; 95% CI, 1.90-3.09) than the patients without the metastasis. We identified significant heterogeneity without publication bias for both outcomes. Moreover, our sensitivity analysis revealed robust estimates were robust for the individual effects. Conclusion: Our findings suggest that patients with colorectal cancer and APN metastases have significantly worse OS and DFS than those without the metastasis. However, inclusion of low-quality retrospective studies with high heterogeneity limits the generalisability of study findings.